Enzyme Inhibitory and Anti-cancer Properties of Moringa peregrina - Shaymaa (Vitae, 2024)
Background: Moringa peregrina is widely used in the traditional medicine of the Arabian Peninsula to treat various ailments, because it has many pharmacologically active components with several therapeutic effects. Objective: This study aimed to investigate the inhibitory effect of Moringa peregrina seed ethanolic extract (MPSE) against key enzymes involved in human pathologies, such as angiogenesis (thymidine phosphorylase), diabetes (α-glucosidase), and idiopathic intracranial hypertension (carbonic anhydrase). In addition, the anticancer properties were tested against the SH-SY5Y(human neuroblastoma). Results: MPSE extract significantly inhibited α-glucosidase, thymidine phosphorylase, and carbonic anhydrase with half-maximal inhibitory concentrations (IC50) values of 303.1 ± 1.3, 471.30 ± 0.3, and 271.30 ± 5.1 µg/mL, respectively. Furthermore, the antiproliferative effect of the MPSE was observed on the SH-SY5Y cancer cell line with IC50 values of 55.1 µg/mL. Conclusions: MPSE has interesting inhibitory capacities against key enzymes and human neuroblastoma cancer cell line.